Communication arts in English for high school (Quezon City : JMC Press, 1998)
Contents--Bk.1. Discovering yourself.--Bk 2. Discovering your Afro-Asia neighbors.--Bk 3. Dicovering your Western friends.--Bk. 4. Discovering one world.
Keywords: Language arts(Secondary)